Inflammatory Dermatopathology A Pathologist's Survival Guide - Billings, Steven D.; Cotton, Jenny; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2011)
Inflammatory Dermatopathology: A Pathologist's Survival Guide provides expert guidance for the reader to develop a systematic approach to the diagnosis of inflammatory disorders of the skin. It covers the most common and clinically important inflammatory disorders of the skin through an image-rich easy to read format. Each section includes practical tips to help navigate the differential diagnosis. Microscopic features are listed as bullet points to enhance readability. Examples of diagnostic comments that practicing pathologists can utilize in their own reports are also provided. Demonstrating a global understanding of inflammatory dermatoses in a quick and efficient manner, Inflammatory Dermatopathology: A Pathologist's Survival Guide will both guide the reader in how to approach inflammatory dermatoses, as well as provide a tool that will help with the writing of surgical pathology reports.
1.Introduction -- 2.Spongiotic Dermatitis -- 3.Psoriasiform Dermatitis -- 4.Interface Dermatitis -- 5.Perivascular Dermatitis -- 6.Vasculitis and Thrombotic Disorders -- 7.Nodular and Diffuse Dermatitis -- 8.Palisading Granulomatous Dermatitis -- 9.Sclerosing Dermatitis -- 10.Bullous Dermatitis -- 11.Panniculitis -- 12.Infections -- 13.Miscellaneous Dermatoses: Invisible Dermatoses and Inflammatory Processes that Clinically Mimic Tumors.
Keywords: Medicine; Dermatology; Pathology; Medicine & Public Health; Pathology; Dermatology